2017
DOI: 10.1002/cyto.a.23247
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating ADCC against adherent cells: Impedance‐based detection is superior to release, membrane permeability, or caspase activation assays in resolving antibody dose response

Abstract: Running headline (45 chars. incl. space) Impedance-based cell analyzer for ADCC Conflicts of interest:None of the authors have conflicts interest. AbstractMonoclonal antibody-based immunotherapeutics will dominate Pharma's next generation of blockbuster drugs, and Fc-associated functions, including antibody dependent cellular cytotoxicity (ADCC) are among the highly desired activities mediated by these antibodies. Therefore, quantitative evaluation of ADCC is required during drug development. Our objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…This cancer cell line was selected as it is known to be resistant to trastuzumab thus representing a clinically challenging cellular model. ECIS proved to be superior to some alternative methods for the quantitation of ADCC in this model [ 14 ]. Therefore, the first optimization assays were run on the ECIS platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This cancer cell line was selected as it is known to be resistant to trastuzumab thus representing a clinically challenging cellular model. ECIS proved to be superior to some alternative methods for the quantitation of ADCC in this model [ 14 ]. Therefore, the first optimization assays were run on the ECIS platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In early studies (8,9), CFSE was shown to be released spontaneously from CFSE‐labeled cells, especially during early time points within 3 or 4 h following initial labeling. In accord with this finding, our data show a significant decrease in CFSE intensity after 4‐h culture and when the target killed by effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, carboxyfluorescein diacetate succinimidyl ester (CFSE), a dye frequently utilized in both in vitro cell proliferation and in vivo cell tracking analyses was used to label the target cells and Hoechst 33258 was used to stain the cell membrane‐compromised cells. As with other cell trace dyes, CFSE has been reported with problems of spontaneous release and leakage from the initial labeling (8,9). A clear discrimination between CFSE labeled target cells and unstained effector cells was shown by analyzing the fluorescence intensity of CFSE‐labeled K562 cells cocultured with PBMNCs (8).…”
mentioning
confidence: 99%
“…A potential drawback of relying on reporter molecules is that they may spontaneously release even from live cells. Impedance-based analysis avoids this issue and has shown promise as a quantitative measure of cell-mediated cytotoxicity that can continuously measure ADCC over time [40]. More recently, scientists have recognized the need for a sensitive, reliable, and accurate cytotoxicity assay that is compliant with regulatory requirements.…”
Section: Measuring Adccmentioning
confidence: 99%